The Effect of Competency on Employee Performance at PT. FSCM Manufacturing Indonesia Plant Filter Cirebon - Kusumah*, Adie Irwan; Sulfiani, Sulfiani; Nurnilasari, Nunung; Heriyono, Heriyono (Riwayat: Educational Journal of History and Humanities, 2024)
Competence is an important factor in determining company performance in order to be able to compete and continue to exist in a competitive market so that companies are required to have competent employees. Through this research, information will be obtained about the extent to which employee competence contributes to performance and helps companies optimize employee competency development, so as to improve overall company performance. This study used a survey method by collecting data from respondents through questionnaires with a sample of 95 people. The data analysis technique in this study used a linear regression test. Competency at PT FSCM Manufaturing Indonesia Plant Cirebon, the highest indicator is showing friendly behavior while the lowest predictor is having leadership traits because employees do not have experience and graduate from high school education. The highest indicator on the employee performance variable is having work absenteeism and while the lowest predictor is having responsibility at work. However, the results showed that significantly competence had a positive effect on employee performance at PT FSCM Manufacturing Indonesia Plant Cirebon because the significance value of the t-test of 0.000 was smaller than alpha () 0.05.